2020
DOI: 10.1109/tmtt.2019.2951166
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Self-Interference in LTE-Advanced and 5G New Radio Wireless Transceivers

Abstract: This article presents a comprehensive survey of the literature on self-interference (SI) in long-term evolution advanced (LTE-A) and fifth-generation (5G) new radio transceivers and should serve the reader as a guide and starting point for further work on SI management. Current trends in cellular transceiver designs are discussed, and reasons why new technologies, such as carrier aggregation, cause potential sensitivity degradation due to self-interfering signals are highlighted. The survey provides an overvie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 79 publications
(75 reference statements)
0
17
0
Order By: Relevance
“…Some terms are redundant, thus, the number of real-valued operations can be reduced slightly. Depending on the available hardware, the frequency shift by f ∆ might be implemented using a multiplication with precomputed complex exponentials or the CORDIC 5 algorithm [49]. The specification of the CSF is provided in Table II, too.…”
Section: A Implementation Of Reference Signal Generationmentioning
confidence: 99%
See 2 more Smart Citations
“…Some terms are redundant, thus, the number of real-valued operations can be reduced slightly. Depending on the available hardware, the frequency shift by f ∆ might be implemented using a multiplication with precomputed complex exponentials or the CORDIC 5 algorithm [49]. The specification of the CSF is provided in Table II, too.…”
Section: A Implementation Of Reference Signal Generationmentioning
confidence: 99%
“…J K is the reversal matrix of size K × K [50]. Similarly to the analysis in [41], the samples of the reference 5 Coordinate Rotation Digital Computer signal are highly correlated and, thus, the Eigenvalue spread of the auto-covariance matrix of x[n] is high for narrow allocations. The TD-LMS is a standard concept to improve the performance of the N-LMS algorithm in such cases [42] by transforming the reference sequence.…”
Section: B Transform-domain Lms Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent studies suggested that the second-order intermodulation (IM) distortion may be significant in wideband transceivers widely used in long-term evolution advanced (LTE-A) and fifth-generation new radio (5G NR) systems [2][3][4][5][6][7]. In direct conversion receivers, also known as homodyne or zero-IF receivers, the second-order IM dominates in degrading the performance of the receiver by causing a severe signalto-interference-plus-noise ratio degradation of the received signal [6,7] because the regenerated second-order distortion is hard to discriminate from the desired signal [8]. Further, the second-order intercept point (IP2), which is used to quantify the second-order distortion regenerated by non-linear sys-tems and devices, appears more frequently in recent amplifier datasheets [9].…”
Section: Introductionmentioning
confidence: 99%
“…In potential applications, as the frequency of the 5G band n78 is approximately twice that of the LTE band B3, when an MS in the dual-connectivity mode transmits signals in the LTE band B3 while receiving in the 5G band n78, its receiver will be severely interfered by the nonlinear interference due to the distortion of the power amplifier (PA) [4]. Specifically, as the transmitted signal in the uplink frequency band comprises the desired transmitted signal (DTS) and mirror frequency interference (MFI) due to the in-phase/quadrature (I/Q) imbalance of the transmitter, the received nonlinear interference in the downlink frequency band includes not only the secondorder harmonics of the DTS and MFI, but also the evenorder intermodulation products (IMP) of the DTS and MFI.…”
Section: Introductionmentioning
confidence: 99%